Critical Discourse Analysis Of The Language Characteristics Of President Prabowo's 2024 Inauguration Speech - Wei Xiong Rui; Anwar Efendi (Cita konsultindo, 2025)
This research examines the linguistic characteristics of President Prabowo Subianto's inauguration speech (October 20, 2024) using a Critical Discourse Analysis (CDA) approach. The primary data consists of the full text of the speech (Setkab RI, 2024). The theoretical framework used includes Fairclough's (1989) three-dimensional model and Teun A. van Dijk's cognitive-discourse approach. The analysis focuses on five dimensions: (1) word choice, (2) rhetorical style (repetition, metaphor, parallelism, historical references), (3) discourse structure, (4) representation of power and inclusive identity, and (5) intertextuality and cultural values. The analysis shows that the speech makes extensive use of populist diction (“people,” “common folk,” pronouns “we,” “brothers and sisters”), repeats key phrases to emphasize the message, and inserts metaphors and cultural proverbs. Its structure is neatly organized: an interfaith greeting at the opening, main themes and narratives, and a closing containing national aspirations. The speaker emphasizes that power comes from the people (“power belongs to the people... We have power, with the people's permission”), stressing Indonesia's inclusive national identity (e.g., “we are all children of Indonesia”). These findings show how state speeches not only convey a vision but also implicitly represent ideology and power relations.